DAERAH GORONTALO DALAM PERUBAHAN POLITIK NASIONAL - Damis, Mahyudin (Universitas Sam Ratulangi, 2019)
This paper represents a cross-time depiction of the status of Gorontalo region, especially pre-independence, post-independence era (Old Order), New Order era until the Reformation Era. Regarding relations between the Central and Regional Governments, Gorontalo has its own record in the eyes of the central government, both with Jakarta and Manado. Although these relatively good relations in the field of governance became social, cultural and political capital for Gorontalo to build a new province, it was not strong enough to deliver its aspirations to get the widest regional autonomy, even though the area was more than half the area of the parent province and its abundant natural resources. In addition, Gorontalo did not have a TNI General (ABRI) during the New Order era who was implementing the